International Parkinson and movement disorder society evidence‐based medicine review: Update on treatments for the motor symptoms of Parkinson's disease - Fox, Susan H.; Katzenschlager, Regina; Lim, Shen‐Yang; Barton, Brandon; de Bie, Rob M. A.; Seppi, Klaus; Coelho, Miguel; Sampaio, Cristina (Movement disorders, 2018)
ABSTRACT Objective: The objective of this review was to update evidence‐based medicine recommendations for treating motor symptoms of Parkinson's disease (PD). Background: The Movement Disorder Society Evidence‐Based Medicine Committee recommendations for treatments of PD were first published in 2002 and updated in 2011, and we continued the review to December 31, 2016. Methods: Level I studies of interventions for motor symptoms were reviewed. Criteria for inclusion and quality scoring were as previously reported. Five clinical indications were considered, and conclusions regarding the implications for clinical practice are reported. Results: A total of 143 new studies qualified. There are no clinically useful interventions to prevent/delay disease progression. For monotherapy of early PD, nonergot dopamine agonists, oral levodopa preparations, selegiline, and rasagiline are clinically useful. For adjunct therapy in early/stable PD, nonergot dopamine agonists, rasagiline, and zonisamide are clinically useful. For adjunct therapy in optimized PD for general or specific motor symptoms including gait, rivastigmine is possibly useful and physiotherapy is clinically useful; exercise‐based movement strategy training and formalized patterned exercises are possibly useful. There are no new studies and no changes in the conclusions for the prevention/delay of motor complications. For treating motor fluctuations, most nonergot dopamine agonists, pergolide, levodopa ER, levodopa intestinal infusion, entacapone, opicapone, rasagiline, zonisamide, safinamide, and bilateral STN and GPi DBS are clinically useful. For dyskinesia, amantadine, clozapine, and bilateral STN DBS and GPi DBS are clinically useful. Conclusions: The options for treating PD symptoms continues to expand. These recommendations allow the treating physician to determine which intervention to recommend to an individual patient. © 2018 International Parkinson and Movement Disorder Society